Implementation CSR PT Pertamina Patra Niaga AFT Minangkabau Toward Kompak Raja Samudera: A Structuration Theory Perspective - Hari Juliansyah; Indraddin; Damsar (Jurnal Sosiologi Nusantara, 2026)
This study examines the implementation of PT Pertamina Patra Niaga AFT Minangkabau's corporate social responsibility (CSR) program in relation to Kompak Raja Samudera. It analyzes it using Anthony Giddens' structuration theory to understand the relationship between agents and structures. The background of this research stems from a social mapping in Ulakan Tapakih District, which identified Nagari Seulayat Ulakan as an area with potential for developing conservation and biodiversity groups, aligning with this CSR program. A descriptive qualitative approach was employed, involving informants from the company, Kompak Raja Samudera, and the Nagari Seulayat Ulakan government. Data were collected through observation, in-depth interviews, and documentation to obtain a comprehensive empirical overview. Research findings indicate that CSR practices can be understood through an enable-and-constrain perspective based on Giddens' structuration theory, in which programs provide opportunities to strengthen the capacity of conservation groups while simultaneously presenting limitations such as restricted access, participation, and program sustainability. This situation reflects the dynamic interaction between agents and structures in implementing community-based CSR. Success in CSR execution is determined by the ability of groups and communities to balance structural support with the maneuvering space of local actors. The implications of this study emphasize the importance of formulating contextual and sustainable CSR policies, as well as the need for further research to examine the long-term sustainability of programs.